Deep Ecology and Biodiversity Conservation: The Ethics of Protecting the Web of Life - Metuonu, Iheanacho Chukwuemeka; Irivike, Festus Enameguono (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Despite increasing environmental advocacy, contemporary conservation ethics remains largely anthropocentric, lacking a robust philosophical foundation for valuing biodiversity intrinsically. This paper addresses that gap by critically appraising Arne Naess’s Deep Ecology, which challenges human-centered environmentalism and advocates an ecocentric framework that affirms the inherent worth of all life forms. The central ethical problem explored is the tension between anthropocentric environmental management and the need for a holistic ethic that respects all beings. Guided by the research question—How can Deep Ecology provide a more ethically consistent foundation for biodiversity conservation than shallow, utilitarian approaches?—this study employs philosophical and conceptual analysis. It systematically engages with Naess’s ecosophy and relevant environmental ethics literature to examine key concepts such as biospheric egalitarianism, relational ontology, and the ecological self. Findings demonstrate that Deep Ecology offers a coherent ethical paradigm grounded in the intrinsic value and interdependence of all life forms. It rejects atomic individualism and redefines human identity as part of the ecological whole, promoting self-realization through identification with nature. The paper also engages with critiques of Deep Ecology, including concerns about impracticality and relativism, while defending its relevance as a transformative ethical vision. The study concludes that adopting an ecocentric ethic rooted in Deep Ecology is essential for sustaining biodiversity and preserving the integrity of the biosphere.